THE EFFECT OF LONGETH RADIATION AND COOL SHOCK DIFFERENTLY TOWARD GINOGENESIS SHEALTHFISH (Ompok rhadinurus Ng) - Ahmad Muttaqie; Nuraini '; Sukendi ' (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2015)
This study was conducted for 28 days from 13 Mei until 9 Juni 2014, In Hatchery and Fish Breeding Laboratory of Fisheries and Marine Sciences University of Riau. The aim of study was to determine of the effect of longeth radiation and cool shock differently toward ginogenesis shealtfish (Ompok rhadinurus Ng) fertilized by spermatozoa catfish (Pangasius hypophthalamus). The experiental used in this study with 1 factor and 10 treatments. The treatment were density of control hybridization and spermatozoa radiation with ultraviolet light (1,2, and 3 minutes) and then performed for 1 minute after conception with cool shock 5oC (1,2 and 3 minutes). The best treatment was combination 3 minutes while radiation performed for 1 minute fertilization with cool shock 5oC for 3 minutes (P3F1K3) with a success percentage of 100%. The water quality parameters along the research period were recorded as temperature 25 – 27oC, pH 5 – 6, and dissolve oxygen ( DO ) 5- 7,5 mg/l respectively.Keywords : Ginogenesis, Long radiation, long cool shock, Ompok radhinurus Ng